Effects of sildenafil citrate on pancreatic and lung complications in an experimental L-arginine-induced acute pancreatitis model - Gulturk, Baris; Bozdag, Ahmet; Ayten, Refik; Cetinkaya, Ziya; Kirkil, Cuneyt; Aygen, Erhan; Ozercan, Ibrahim Hanifi (Termedia Publishing House Ltd, 2021)
Aim: In this study, we aimed to investigate the effects of sildenafil citrate on acute pancreatitis and pulmonary complications of the disease. Material and methods: In this study, we used 21 male Wistar-Albino rats weighing between 185 and 230 g. The rats were divided into 3 groups. Group 1 rats (control group, n = 7) were administered intraperitoneal 0.9% NaCl injection. Group 2 (study group, n = 7) and Group 3 (treatment group, n = 7) rats were given 100 mg/100 gr L-arginine twice, with an interval of 1 h to create acute pancreatitis. Group 3 was also administered intraperitoneal 10 mg/kg/day sildenafil citrate in 2 equal doses, 30 min and 12 h after creation of AP. The pancreas and lungs of all rats were stained with haematoxylin and eosin and examined histopathologically. Aspartate aminotransferase (AST), alanine aminotransferase (ALT), lactate dehydrogenase (LDH), interleukin (IL) 1 alpha (IL-1 alpha), IL-6, tumor necrosis factor alpha (TNF-alpha), nitric oxide (NO) and ADMA levels were measured in blood samples. Results: In the treatment group, levels of amylase, AST, ALT, LDH, IL-1, IL-6, TNF-alpha, and NO were lower. In addition, pancreas and lung oedema, and perivascular inflammation were significantly less on histopathological examination when compared to the study group (p < 0.001). The ADMA level was significantly higher in the treatment group when compared to the control and study groups. There was no acinar cell necrosis or haemorrhage in the treatment group. However, the difference was not regarded as statistically significant because sufficient acinar cell necrosis and haemorrhage could not be created in the study group. Conclusions: Sildenafil citrate significantly decreases various biochemical and histopathological changes in the early phase of acute pancreatitis and protects pancreatic tissue.
Keywords: acute pancreatitis; L-arginine; pancreatitis complications; sildenafil